THE EFFECT OF COOPERATIVE INTEGRATED READING COMPOSITION (CIRC) TECHNIQUE TOWARD STUDENT READING COMPREHENSION ON RECOUNT TEXT AT GRADE VIII MTS NURUL IMAN ULU GEDONG - Abadi, Ayuliamita; Raudhatul Jannah, Siti; Andriani, Meri (JR-ELT (Journal of Research in English Language Teaching), 2020)
The four basic English skills are speaking, listening, reading, and writing. Receptive skills are reading and listening, productive skills are speaking and writing. Reading establishes textual meaning in language. Reading is a vital ability for English learners. It's important since reading helps pupils learn a lot. The first issue with this study was students' low vocabulary. Second, students lack reading motivation. Third, kids think their reading has no relation to the word. Fourth, the teacher applies old reading strategies without student participation. This study examined how the Cooperative Integrated Reading Composition Technique affected reading comprehension on recount texts in grade VIII at MTS Nurul Iman Ulu Gedong. There were 54 students in this study. In the experiment, 28 class VIII pi were utilized to sample. In this study, the mean pre-test score was 63,21 and the post-test score was 79,10 (79,10>63,21). At 27 degrees of freedom and 5% significance. Table values are 2.052 and t-test values are 0.54 (0,54â‰¥2,052). It showed Hi accepted and Ho declined. Thus, the study advised English teachers to employ Cooperative integrated reading composition (CIRC) to teach reading comprehension, particularly recount text.